2006
DOI: 10.1126/science.1119133
|View full text |Cite
|
Sign up to set email alerts
|

New Neurons Follow the Flow of Cerebrospinal Fluid in the Adult Brain

Abstract: In the adult brain, neuroblasts born in the subventricular zone migrate from the walls of the lateral ventricles to the olfactory bulb. How do these cells orient over such a long distance and through complex territories? Here we show that neuroblast migration parallels cerebrospinal fluid (CSF) flow. Beating of ependymal cilia is required for normal CSF flow, concentration gradient formation of CSF guidance molecules, and directional migration of neuroblasts. Results suggest that polarized epithelial cells con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
595
1
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 701 publications
(621 citation statements)
references
References 19 publications
15
595
1
10
Order By: Relevance
“…The role of CSF in the regulation of the adult neural stem cell is unknown, but recently it has been shown that the flow of the CSF generated by the ciliated ependymal cells in the adult CNS is critical in establishing a gradient of molecules (such as slit), which play a role in the directional migration of their daughter neuroblasts (Sawamoto et al, 2006).…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 99%
“…The role of CSF in the regulation of the adult neural stem cell is unknown, but recently it has been shown that the flow of the CSF generated by the ciliated ependymal cells in the adult CNS is critical in establishing a gradient of molecules (such as slit), which play a role in the directional migration of their daughter neuroblasts (Sawamoto et al, 2006).…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 99%
“…In addition, two rodent models for hydrocephalus (the WIC-Hyd rat and SUMS/ NP mouse) have ciliary defects although the mutated genes are not currently known [Bruni et al, 1988;Torikata et al, 1991]. Intriguingly a very recent report indicates that cerebrospinal fluid flow, driven by the motile cilia of ependymal cells, establishes a chemical gradient within the subventricular zone, and is required for the correct migration of neuroblasts in adult mouse brain [Sawamoto et al, 2006]. This suggests a further mechanism by which defects in ependymal ciliary motility might have a direct effect on neuronal development.…”
Section: Efhc1 Mutations and Juvenile Myoclonic Epilepsymentioning
confidence: 99%
“…Directional migration cues, which are relevant following neural injury, include members of the chemokine family, such as CXCL12/CXCR4 [14][15][16]. Axon guidance molecules, such as Slits [17,18] and other factors [19,20], also play a role in the directed NPC migration along the RMS, along with chemoattractive agents secreted from the OB such as sonic hedgehog [21] or secreted or membranebound factors on the astrocytic glial tube that surrounds the NPCs in the RMS [22,23].…”
Section: Introductionmentioning
confidence: 99%